2012
DOI: 10.4209/aaqr.2011.11.0213
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Innovative Circulating Fluidized-Bed with Microwave System for Controlling NOx

Abstract: Selective catalytic reduction (SCR) and selective non-catalytic reduction (SNCR) technique are widely used to control nitrogen oxides emissions. However, both techniques have a general shortcoming known as NH 3 slip.This research introduced the design of activated carbon in a circulating fluidized-bed with microwave system and developed an innovative de-NO x technique. The whole system demonstrated the capability and advantage of reducing reductant cost and continuous process. The experiments investigated micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…An innovative de-NO x technology has also been developed by Yuan-Yi Chang et al using activated carbon in a circulating fluidized-bed reactor, with the adoption of microwaves for the regeneration of the activated carbon, with the aim of increasing the adsorption and destruction efficiency and decreasing the energy consumption [195]. The results of the study suggested that the MW process may be more effective than the traditional methods because an increase in the specific surface areas of activated carbon was found with the increase of MW power, generating an increase in NO x adsorption capacity and rate.…”
Section: Environmental Catalysismentioning
confidence: 99%
“…An innovative de-NO x technology has also been developed by Yuan-Yi Chang et al using activated carbon in a circulating fluidized-bed reactor, with the adoption of microwaves for the regeneration of the activated carbon, with the aim of increasing the adsorption and destruction efficiency and decreasing the energy consumption [195]. The results of the study suggested that the MW process may be more effective than the traditional methods because an increase in the specific surface areas of activated carbon was found with the increase of MW power, generating an increase in NO x adsorption capacity and rate.…”
Section: Environmental Catalysismentioning
confidence: 99%
“…Furthermore, combustion sources [4,5] and chemical processes [2] enhanced the N 2 O production [6][7][8][9]. There are numerous methods can be employed for N 2 O reduction which includes: thermal decomposition [10][11][12][13], selective adsorption [14][15][16], the application of microwave plasma technology [17][18][19], and catalytic destruction [20,21]. Among them, catalytic destruction has advantages compare to alternative technologies for controlling N 2 O emissions, for example, low energy costs when compared with thermal decomposition [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The polarization causes the molecules to be at a higher energy state that brings about more impacts among the reactant molecules, and faster decomposition of pollutants occur (Zhang et al, 2007;Chang et al, 2012). The MW heating is based on using media with higher dielectric loss that is related to its own dipole orientation.…”
Section: Cb Removal Efficiency For Plain Cordierite With Mw Irradiationmentioning
confidence: 99%
“…Microwave (MW) is an electro-magnetic radiation with frequencies ranging from 300 MHz to 300 GHz (Chang et al, 2012;Woo, Grippin, Wu, & Wander, 2012). The MW absorbed by a solution will cause non-thermal effect to reduce the activation energy and weaken the chemical bonds of the organic chemicals (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%